Printable Organic PIN Phototransistor and Its Application for Low Power and Noise Imaging Detection - Zhi Tao (IEEE, 2022)
The power consumption and the opto-electric noise of organic photo-detectors are the challenges for large-scale detecting and imaging applications to surpass. This article presents a new device concept of organic heterojunction PIN channel for photo-transistor. The presence of the channel's heterostructure enables rectifying capability and effective control of defect density, which leads to low power consumption (0.12 to 7.5 nW) and low dynamic noise (4.5 × 1013 Jones detectivity). Significantly, through adopting the highly efficient Perovskite Quantum Dots as intrinsic sensing core, the device exhibits high responsivity up to 7190 A/W. As we demonstrate a large-scale 10 × 20 imaging array with integrated photo-transistor, the output signals are read-out and rebuilt by I-V converting amplifier with analog-to-digital circuit and numerical computation method to visualize the functionality of the system.